1989
DOI: 10.1007/bf00718648
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of metallothionein in human testicular embryonal carcinoma cells

Abstract: The presence of high levels of metallothionein (MT) in developing mammalian cells is well documented. It has been suggested that the developmental profile and gene expression of MT is similar to that of the so-called oncodevelopmental gene products such as a-fetoprotein. In this study tissue sections of nine human embryonal carcinomas of the testis were tested by means of the avidin-biotin peroxidase complex for the presence of MT. The antigen was localized in variable amounts in the cytoplasm and nucleus in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…The differences in metallothionein localization in 4: '. ,I S embryonal carcinoma cells are closely related to their well-defined histomorphological patterns (19). This study showed that tumors with a typical glandular-papillary pattern, corresponding to the epiblastic or ectodermal pattern were strongly positive for metallothionein, while tumors growing in solid masses, designated embryoblastic, were negative or weakly positive for metallothionein at the periphery.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…The differences in metallothionein localization in 4: '. ,I S embryonal carcinoma cells are closely related to their well-defined histomorphological patterns (19). This study showed that tumors with a typical glandular-papillary pattern, corresponding to the epiblastic or ectodermal pattern were strongly positive for metallothionein, while tumors growing in solid masses, designated embryoblastic, were negative or weakly positive for metallothionein at the periphery.…”
Section: Introductionmentioning
confidence: 68%
“…The immunohistochemical staining of metallothionein in various tumors showed its presence mainly in epithelial cells, especially on the proliferating edge of the tumor (19). There was a distinct difference between metallothionein staining in seminomas and nonseminomas in human testicular tumors (Table 2).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The lower zinc in pancreatic endocrine neoplasms may require less MT for homeostasis and detoxification; however, the exact reason for the lower content of MT in pancreatic endocrine neoplasms is unknown. MT levels are elevated in certain tumors (20,21), including breast cancers (22,23), prostate carcinomas (24,25), testicular embryonal carcinomas (26), renal cell carcinomas (27), thyroid tumors (28), brain tumors (29), and others (2, 21, 30, 31). MT overexpression has been implicated in resistance to radiotherapy (31) and toxicity to chemotherapy (32).…”
Section: Discussionmentioning
confidence: 99%